2022
DOI: 10.2147/cmar.s360473
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Immune-Related Adverse Events and Efficacy and Changes in the Relative Eosinophil Count Among Patients with Advanced Urothelial Carcinoma Treated by Pembrolizumab

Abstract: Background To evaluate the association between immune-related adverse events (irAEs) and the clinical outcomes and also between irAEs and the post-treatment changes in the relative eosinophil count (REC) in advanced urothelial carcinoma (UC) patients treated with pembrolizumab. Materials and Methods This retrospective study analyzed 105 advanced UC patients treated with pembrolizumab after disease progression on platinum-based chemotherapy between January 2018 and June … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…[17][18][19][20] Although the detailed underlying mechanisms about association between eosinophils and irAEs occurrence are unclear, previous studies supported our data that increased eosinophils may reflect efficacy and safety in patients treated with ICIs. 16,18,[24][25][26][27]38 In the past, most studies have shown that ICImediated irAEs may be associated with an improved response to therapy and survival outcomes in several types of cancers. [43][44][45][46] Consistently, our data revealed significantly longer mOS and mPFS in patients with irAEs than in those without irAEs, as reported in another study (Figure 4A,B).…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] Although the detailed underlying mechanisms about association between eosinophils and irAEs occurrence are unclear, previous studies supported our data that increased eosinophils may reflect efficacy and safety in patients treated with ICIs. 16,18,[24][25][26][27]38 In the past, most studies have shown that ICImediated irAEs may be associated with an improved response to therapy and survival outcomes in several types of cancers. [43][44][45][46] Consistently, our data revealed significantly longer mOS and mPFS in patients with irAEs than in those without irAEs, as reported in another study (Figure 4A,B).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a positive association between eosinophil invasion of tumor tissue or an increase in PBEC and superior response to ICIs in several types of cancer has been reported. 20 , 37 Although the underlying mechanism is not fully understood, there is strong evidence that eosinophils exhibit antitumor effects. Thus, eosinophils affect the immune response to diseases such as cancer, and predictive biomarkers that reflect this inflammatory response to treatment may be useful for clinical decision-making in the management of patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, including studies on advanced UC, have reported a possible association between the incidence of irAEs and the clinical efficacy of ICIs. [28][29][30] In the PS ≥2 group, the shorter OS may have been due to the lower incidence of irAEs. In addition, interestingly, patients with PS ≥2 did not show a change of eosinophils, increase of REC, and decrease NER, while these values showed significant changes in patients with PS 0-1.…”
Section: Discussionmentioning
confidence: 99%